Moving towards a deforestation-free cacao and chocolate value chain with low greenhouse gas emissions - Ivanova, Yovita; Tristán Febres, María Claudia; Romero Sánchez, Miguel Antonio; Charry, Andres; Lema, Sebastián; Choy, José Sánchez; Vélez Betancourt, Andrés Felipe; Castro Nuñez, Augusto; Quintero, Marcela (International Center for Tropical Agriculture, 2020)
The report "Towards a cocoa and chocolate chain free of deforestation and low in greenhouse gas emissions: Current status, opportunities with a value chain approach and plan of action" presents an input for the development of a cocoa chain free of deforestation and low in greenhouse gas (GHG) emissions in the Ucayali region. The document has been produced under the framework of the Sustainable Amazon Businesses (SAB) project, led by CIAT as part of the Bioversity International and CIAT Alliance, in coordination with the Ministry of the Environment (MINAM) and the Ministry of Agriculture and Irrigation (MINAGRI) of Peru, and in partnership with the international consulting firm Climate Focus (CF). This project is part of the International Climate Initiative (IKI), supported by the German Federal Ministry for the Environment, Nature Conservation, and Nuclear Safety (BMU). The present plan aims to contribute to the effort of the Regional Government of Ucayali (GOREU) to reduce GHG emissions from the agricultural sector due to changes in land use in the Peruvian Amazon, in accordance with the Peruvian Government's international commitments to mitigate climate change. The document presents an innovative and novel plan to contribute to the environmental sustainability of the cacao and chocolate value chain, developed from the perspective of forest conservation and the recovery of degraded ecosystems and with solutions provided by value chain actors. The plan contributes to the Peruvian Government's efforts to comply with the National Determined Contributions (NDC) assumed at the Conference of the Parties - COP21 and the agreement between the Governments of Norway, Germany and Peru - Joint Declaration of Intent (JDI) - two commitments that seek to reduce GHGs. It also seeks to promote the development of national plans, policies and programs with a view to achieving the Sustainable Development Goals (SDA) and Agenda 2030, which recognize that agriculture and climate change cannot be considered separately, and therefore call for a coherent and integrated approach to sustainability in the agriculture and environment sectors. This report provides information on the cocoa and chocolate chain that is as up-to-date as possible and very useful for the national and regional government, industry, producers, nongovernmental organizations and international cooperation agencies that are currently working on a chain that will contribute to the sustainable development of agriculture in the Peruvian Amazon. For the development of this document designed and agreed with key actors in the sector, the project has signed a framework cooperation agreement with GOREU. Through this cooperation, the articulation of this document with the most relevant development and territorial planning and production instruments in the region has been verified. Furthermore, it is expected that the specific elements of this document will contribute to the achievement of the objectives set out in the main management instruments of the Ucayali region and climate change in the country, among others: the Concerted Regional Development Plan (PDRC), the Regional Climate Change Strategy (ERCC) and the Low Emission Rural Development Strategy (ERBE). Based on this report, the SAB project intends to accompany the design and implementation of a pilot business model in the cocoa and chocolate chain, which will materialize several of the elements of this report, while taking advantage of emerging financial and market opportunities for products that are free of deforestation and low in GHG emissions. It is expected that this business model and its subsequent conversion into an investment model can serve for replication and scaling up in the region and in the country and, likewise, contribute with references of deforestation-free business models at the international level. Furthermore, it is expected that these models will serve as a basis for the generation of public policies that contribute to the sustainability of the sector.